Evaluation of antiulcer and antioxidant potential of Ipomoea Reniformis leaf extract against experimentally induced ulcer in rats - S., Shree Lakshmi Devi; S. C., Abilash; S., Sengottuvelu (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Ulcer is a major disease of gastrointestinal system which affects about 10% of the world’s population. As conventional drugs can produce undesirable side effects on long term use it can be replaced by herbal medicines more safely. The study was designed to evaluate the antiulcer activity of ethanolic leaf extract of Ipomoea reniformis against pyloric ligated ulcer and cold restraint stress induced ulcer models in rats. Methods: Male Wistar albino rats were used. 0.1% Carboxy Methyl Cellulose (CMC) was used as vehicle. Ethanolic leaf extract of Ipomoea reniformis was employed at two dose levels (200 and 400mg/kg). Omeprazole (10mg/kg) was used as reference control in both the models. The test drugs were administered by suspending in CMC, through oral route. In pyloric ligated ulcer model, gastric volume, ulcer index and percentage protection were measured. In cold restraint stress induced ulcer model, ulcer index and percentage protection was measured. The stomach homogenate was subjected to antioxidant profiles. Results: Ethanolic leaf extract of Ipomoea reniformis dose dependently decreased the gastric volume in pyloric ligated ulcer model and significantly reduced the ulcer index in both the models. Ipomoea reniformis in both the doses significantly protected the animals against stress-induced free radical damage due to decrease in LPO and reversal of changes induced by stress on SOD and CAT. Conclusions: From the result, it was concluded that the Ipomoea reniformis leaf extract exhibited antiulcer activity in both the tested models were due to its antisecretary and antioxidant property.